Reappraisal of the Climate Impacts of Ozone‐Depleting Substances. Issue 20 (13th October 2020) - Morgenstern, Olaf; O'Connor, Fiona M.; Johnson, Ben T.; Zeng, Guang; Mulcahy, Jane P.; Williams, Jonny; Teixeira, João; Michou, Martine; Nabat, Pierre; Horowitz, Larry W.; Naik, Vaishali; Sentman, Lori T.; et al.
Abstract: We assess the effective radiative forcing due to ozone‐depleting substances using models participating in the Aerosols and Chemistry and Radiative Forcing Model Intercomparison Projects (AerChemMIP, RFMIP). A large intermodel spread in this globally averaged quantity necessitates an "emergent constraint" approach whereby we link the radiative forcing to ozone declines measured and simulated during 1979–2000, excluding two volcanically perturbed periods. During this period, ozone‐depleting substances were increasing, and several merged satellite‐based climatologies document the ensuing decline of total‐column ozone. Using these analyses, we find an effective radiative forcing of −0.05 to 0.13 W m −2 . Our best estimate (0.04 W m −2 ) is on the edge of the "likely" range given by the Fifth Assessment Report of IPCC of 0.03 to 0.33 W m −2 but is in better agreement with two other literature results. Plain Language Summary: Chloroflourocarbons and other compounds involved in ozone depletion are also powerful greenhouse gases, but their contribution to global warming is reduced due to the cooling effect of the ozone loss which they induce. Models informing an upcoming climate report disagree on the ozone loss and thus on the climate influence of these gases. Here we use observed ozone loss to reduce the resultant uncertainty in their overall climate influence and infer a smaller warming influence of these substances than was considered likely in a 2013 climate report. The result implies a smaller benefit to climate due to their phase‐out, mandated under the Montreal Protocol, than would have been the case under previous understanding. Key Points: Effective radiative forcing of ozone‐depleting substances, as discerned from CMIP6 simulations, spans a large range Using an emergent constraint approach, our new estimate is consistent with observational climatologies of total‐column ozone This range implies a smaller forcing than the estimate provided by the Fifth Assessment Report of the Intergovernmental Panel on Climate Change